1998
DOI: 10.1117/12.331361
|View full text |Cite
|
Sign up to set email alerts
|

<title>Comparison of wavelet-based and statistical speckle filters</title>

Abstract: The wavelet transform has become a very popular tool in signal and image processing. Over the last few years, several authors have proposed wavelet-based filters for speckle reduction in SAR* images, and the results are generally reported to be superior to those obtained with traditional statistical speckle filters. In this paper we give a thorough experimental comparison of representative filters from both categories. We show that spatially adaptive statistical filters yield beter noise reduction and preserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Filtering in the transform domain has been extensively used during the last twenty years, such as wavelet transform [9,10,11,12], principal component analysis [13,14] and sparse representation [15,16,17]. Wavelet shrinkage can be readily applied to SAR despeckling after a homomorphic transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filtering in the transform domain has been extensively used during the last twenty years, such as wavelet transform [9,10,11,12], principal component analysis [13,14] and sparse representation [15,16,17]. Wavelet shrinkage can be readily applied to SAR despeckling after a homomorphic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Each wavelet subband is associated to a speckle contribution that may be exactly measured. Classical hard-thresholding and soft-thresholding methods are applied in [9,10], respectively. Some scholars [18,19,20] have performed a statistical Bayesian estimation to optimize the shrinkage parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above, we also implemented a filter based on adaptable masks (Oddy [1]) and wavelet based Soft Thresholding [3], to show the implementability of these classes of methods in our framework.…”
Section: Figmentioning
confidence: 99%
“…Common despeckling methods include convolution filters (Mean, Gauss), rank operators (Median), methods based on local statistics (Lee, Kuan, Frost, Gamma MAP), filters with adaptable masks (Oddy), and wavelet based methods (Soft Thresholding). Reviews and comparisons of these methods are available in [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Gagon and Jouan [3] have used elliptic soft thresholding and shown that the waveletbased approach is better than the standard spatial domain filters. Nevertheless, log-transformation is a nonlinear operation, and thus provides a denoised image with a biased mean intensity [6].…”
Section: Introductionmentioning
confidence: 99%